Educación financiera con enfoque sostenible y transformativo para el gremio ganadero del municipio de Arauquita, (Arauca) (2022)
This project analyzes the lack of financial education, in a transformative and sustainable ecosystem for livestock in the municipality of Arauquita, in the department of Arauca